Promoting entrepreneurship in science education: Insights into curricular goals - Karampelas, Konstantinos (Trends in Computer Science and Information Technology, 2022)
This study aims to examine whether elementary science curricula can be combined with the teaching of entrepreneurship, based on the approach of Lackéus, which is considered an important point of focus for present-day education systems. Entrepreneurship is not commonly handled as an autonomous subject. According to relevant approaches, teaching entrepreneurship relies on certain competencies, knowledge, skills, and attitudes. This research aims to identify whether science curricula include these competencies and can assist in developing entrepreneurial qualities. The data for the research was derived from the science curricula of 16 different countries or regions. Findings showed that there are entrepreneurial competencies in the curricula examined.